Geologic Slip‐Rate Determinations on the Talas‐Fergana Fault: Mismatch With Geodetic Slip Rate. Issue 9 (4th May 2018) - Rust, Derek; Korzhenkov, Andrey; Tibaldi, Alessandro
Abstract: Detailed new paleoseismic field investigations at two sites on the Talas‐Fergana fault, a poorly known strike‐slip structure that transects the Tien Shan mountain range, document late Holocene slip rates of 11–1 6 mm a −1 . This prominent structure is distinctive in striking obliquely NW‐SE across the Tien Shan, which is otherwise dominated by contractional structures striking generally E‐W. Moreover, a satellite‐based Global Positioning System network spanning the Tien Shan orogen records active N‐S contraction rates of 20 mm a −1, but limits slip on the Talas‐Fergana fault to <2 mm a −1 . This profound mismatch between long‐term geologic and short‐term geodetic slip rates, which may suggest temporal variability in slip, highlights the importance of field‐based investigations as a complement to remotely sensed data, particularly in evaluating models of lithosphere behavior and earthquake probabilities on presently locked faults such as the Talas‐Fergana. Plain Language Summary: The 700 km long Talas‐Fergana fault is one of several large faults linked to the collision between the Indian and Eurasian tectonic plates and cuts obliquely across the Tien Shan mountain range north of the Himalayas. Satellite‐based Global Positioning System data show that the Tien Shan range is being rapidly compressed tectonically, at the rate of about 20 mm per year, yet indicate a slip rate on the Talas‐Fergana of less than 2 mm per year. However, our study employs intensive field geologic techniques to determine that the slip rate on this fault has averaged 11–16 mm per year over recent millennia. With increasing reliance on satellite‐based measurements investigating such a profound mismatch is important for reliable earthquake hazard assessments on the Talas‐Fergana fault, which appears locked and is at an unknown point in its earthquake cycle. Reconciling the two data sets suggests significant variability in slip rate on the Talas‐Fergana through time, a conclusion that may have additional implications for models of lithosphere behavior. Key Points: Documents Talas‐Fergana fault slip‐rate using extensive paleoseismic trenching investigations Fills gap in field‐based deformation rate data associated with India‐Asia collision Highlights a mismatch that has important implications for assessing earthquake probabilities and modeling lithosphere behavior